Clinical and bi-genomic DNA findings of patients suspected to have mitochondrial diseases - Gedikbasi, Asuman; Toksoy, Guven; Karaca, Meryem; Gulec, Cagri; Balci, Mehmet Cihan; Gunes, Dilek; Gunes, Seda; Aslanger, Ayca Dilruba; Unverengil, Gokcen; Karaman, Birsen; Basaran, Seher; Demirkol, Mubeccel; et al. (Frontiers in Genetics, 2023)
Background: Mitochondrial diseases are the most common group of inherited metabolic disorders, causing difficulties in definite diagnosis due to clinical and genetic heterogeneity. Clinical components are predominantly associated with pathogenic variants shown in nuclear or mitochondrial genomes that affect vital respiratory chain function. The development of high-throughput sequencing technologies has accelerated the elucidation of the genetic etiology of many genetic diseases that previously remained undiagnosed. Methods: Thirty affected patients from 24 unrelated families with clinical, radiological, biochemical, and histopathological evaluations considered for mitochondrial diseases were investigated. DNA isolated from the peripheral blood samples of probands was sequenced for nuclear exome and mitochondrial DNA (mtDNA) analyses. MtDNA sequencing was also performed from the muscle biopsy material in one patient. For segregation, Sanger sequencing is performed for pathogenic alterations in five other affected family members and healthy parents. Results: Exome sequencing revealed 14 different pathogenic variants in nine genes encoding mitochondrial function peptides (AARS2, EARS2, ECHS1, FBXL4, MICOS13, NDUFAF6, OXCT1, POLG, and TK2) in 12 patients from nine families and four variants in genes encoding important for muscle structure (CAPN3, DYSF, and TCAP) in six patients from four families. Three probands carried pathogenic mtDNA variations in two genes (MT-ATP6 and MT-TL1). Nine variants in five genes are reported for the first time with disease association: (AARS2: c.277C>T/p.(R93*), c.845C>G/p.(S282C); EARS2: c.319C>T/p.(R107C), c.1283delC/p.(P428Lfs*); ECHS1: c.161G>A/p.(R54His); c.202G>A/p.(E68Lys); NDUFAF6: c.479delA/p.(N162Ifs*27); and OXCT1: c.1370C>T/p.(T457I), c.1173-139G>T/p.(?). Conclusion: Bi-genomic DNA sequencing clarified genetic etiology in 67% (16/24) of the families. Diagnostic utility by mtDNA sequencing in 13% (3/24) and exome sequencing in 54% (13/24) of the families prioritized searching for nuclear genome pathologies for the first-tier test. Weakness and muscle wasting observed in 17% (4/24) of the families underlined that limb-girdle muscular dystrophy, similar to mitochondrial myopathy, is an essential point for differential diagnosis. The correct diagnosis is crucial for comprehensive genetic counseling of families. Also, it contributes to making treatment-helpful referrals, such as ensuring early access to medication for patients with mutations in the TK2 gene.